1983
DOI: 10.1139/o83-060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat shock on synthesis and phosphorylation of nuclear and cytoplasmic proteins in the fungus Achlya

Abstract: Heat shock induced by an increase in temperature from 28 to 37 degrees C led to changes in synthesis and phosphorylation of cytoplasmic and nuclear proteins in the aquatic fungus Achlya. In the cytoplasmic fraction a marked increase in [35S]methionine labelling of proteins in the molecular weight range of 96 000, 85 000, 74 000, and 70 000 was observed. Two-dimensional electrophoresis resolved each of these classes of proteins into several components. Major changes in the nuclear fraction included the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
39
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 18 publications
3
39
0
Order By: Relevance
“…Nuclei in the heat-shocked cells, but not in control cells, exhibited marked chromatin condensation and contained bundles of filaments which were approximately 4 nm in diameter. Concomitantly, the bulk of chromatin from heat-shocked nuclei showed a decreased sensitivity to digestion with the enzyme DNase I relative to chromatin from control cells.We have previously reported that in the aquatic fungus Achlya ambisexualis at least 10 molecular weight classes of proteins (96,000 [96K], 85K, 70K to 74K, 43K, 28K, 27K, 24K, 23K, and 18K) are synthesized within 20 to 60 min after a rapid elevation of temperature (heat shock) from 28 to 37°C (29,30). This heat shock response was accompanied by changes in the levels of phosphorylation of several nuclear proteins, including acid-insoluble proteins, as well as the apparent marked phosphorylation of two Achlya histones.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Nuclei in the heat-shocked cells, but not in control cells, exhibited marked chromatin condensation and contained bundles of filaments which were approximately 4 nm in diameter. Concomitantly, the bulk of chromatin from heat-shocked nuclei showed a decreased sensitivity to digestion with the enzyme DNase I relative to chromatin from control cells.We have previously reported that in the aquatic fungus Achlya ambisexualis at least 10 molecular weight classes of proteins (96,000 [96K], 85K, 70K to 74K, 43K, 28K, 27K, 24K, 23K, and 18K) are synthesized within 20 to 60 min after a rapid elevation of temperature (heat shock) from 28 to 37°C (29,30). This heat shock response was accompanied by changes in the levels of phosphorylation of several nuclear proteins, including acid-insoluble proteins, as well as the apparent marked phosphorylation of two Achlya histones.…”
mentioning
confidence: 99%
“…Before labeling, cells were collected by filtration, transferred to a phosphate-reduced (0.004 mM) mating medium described by Barksdale and Lasure (2) and allowed to equilibrate for 2 h. All cells were prelabeled at 28°C with 12 i,Ci of carrier-free 32P, per ml (New England Nuclear Corp.) for 30 min. Cells were then either maintained at 28°C for an additional 60 min (control) or subjected to a rapid elevation of the temperature to 37°C as described previously (29,30) and then maintained at 37°C for an additional 60 min (heat shock). Thus, the total labeling period in the presence of 32p; for both control and heat-shocked cultures was 90 min.…”
mentioning
confidence: 99%
See 3 more Smart Citations